Peculiarities of FDI performance in developed, developing and underdeveloped countries - Tvaronavičienė, Manuela; Lankauskienė, Toma (Business: Theory and Practice, 2011)
The aim of this article is to evaluate impact of FDI on sustainable development indicators of differently developed countries during two periods of time: a time span before (2000−2007) and a time span embracing the global economic crisis period (2000–2009). Reviewed ample supply of relevant scientific literature made a presumption to arise that the impact of FDI differs in developed, developing and underdeveloped countries, i.e. depends on the level of development: developed countries benefit most, developing less and underdeveloped least. Countries are attributed to respective groups according to their level of development and indicators are chosen for investigation. The following indicators capable of reflecting FDI impact on enhancing wellbeing in unevenly developed countries are: GDP, exports, inflation, population, life expectancy at birth, primary school pupils, infant mortality, total health expenditure per capita, total tax rate, internet users, residential consumption of electricity , and differences between developed and underdeveloped countries in the field of economic, social, business environment are taken into account. Several other hypotheses have been formulated and FDI impact on sustainable development indicators has been estimated with the help of empirical research in order to test the initial presumption. Obtained results enabled to compare peculiarities of FDI performance during two periods of time.